Behavior of marine fishes : capture processes and conservation challenges - He, Pingguo (Wiley-Blackwell, 2010)
Understanding fish behavior in relation to capture processes in marine fisheries is of fundamental importance to reducing bycatch and discards, and to enhancing marine fisheries conservation efforts.